Motivations of service providers to participate in sharing economy platform: An exploratory study of AirBnB hosting experience in Vietnam - Tang, D.B.Tran (2018)
This exploratory research aims to provide theoretical contributions and managerial recommendations to understand the service providers’ motivations in Sharing economy platform. Considering a P2P platform enables interactions among two or more stakeholders included: users and providers and the platform owner as being at the centre of an ecosystem (Hagiu and Wright, 2015), this research takes into account the provider’s motives of participating in AirBnb, the most predominant practice in accommodation sharing domain of SE. Besides, the study focuses on examining the AirBnb hosts’ motivation in the context of a developing country - Vietnam. The main theoretical frameworks informed this study were combinations of altruism and utilitarian motivations framework (Belk, 2007, Bucher et al, 2016, Bocker & Meelen, 2016) and economic - social - environmental motivations framework (Bardhi and Eckhardt, 2012, Hamari et al, 2016, Tussyadiah, 2016). Most parts in the framework were reflected under the umbrella of Self-determination theory (SDT) (Deci & Ryan, 2000) which classified the human motivation by intrinsic and extrinsic domains. Whilst there is minor drivers explained by another theory of motivation - Theory of Planned Behaviour (Ajzen, 1991). The elementary data and findings collected mostly from 20 semi-structured interviews with the AirBnb hosts or used-to-be one. Besides, there are secondary data sources considered to provide a more comprehensive outlook of AirBnb market from AirDna.com - a website provides AirBnb market insights and figures, as well netnography technique to observe the key behaviours and motivation on online community of AirBnb host (Facebook group of AirBnb hosts in Vietnam) as an initial source of references and assumptions at the beginning stage of the research. From the theoretical perspective, the research findings found to provide a more holistic understanding of the motivations for participation in the sharing economy by focusing on the providers’ motivation to narrow the knowledge gap in the extant literatures. The notable interesting findings obtained from the research were the “personalization / self- exposure” motivation; the “other stakeholders’ development and well-being” motivation which hardly revealed in extant literatures. The heterogeneity of the motivations is also an interesting findings. There no motivations are completely utilitarian or altruism but rather a complex motives combined with both extrinsic and intrinsic motives, or could refer to “purposive” altruism or in other words “reciprocal altruism”. The different dimensions of three key motives: economic - social - environmental motivations are also explored